Computational fluid dynamics simulation of laboratory scale reactor of fast pyrolysis fluidised bed - Seyed, Amirmostafa Jourabchi; Tan, Zhong Jian (IOP Publishing, 2017)
Euler-Eulerian two-fluid model (EE-TFM), among the computational fluid dynamics (CFD) techniques and module available on the market, have been chosen to study and obtain the operational parameters required for the fluidisation of different materials and different particle diameters of the fluidised bed model. In the present work, the effect of the material, namely stainless steel and sand with the respective diameters of 0.5 and 1 mm have been investigated with the aid of ANSYS FLUENT 15. From the simulation, it has found that the minimum required superficial velocity of the driving gas for fluidisation of steel beads are 70 cm/s and 140 cm/s respectively for diameter of 0.5 and 1.0 mm. On the other hand, the minimum required superficial velocities to fluidise the less dense sand beads are 30 cm/s and 70 cm/s for particle diameter of 0.5 and 1.0 mm respectively. The results show that the minimum fluidisation velocity increases as the density of the particle material increases; while it also increases, when the particle diameter increases. It is concluded that the drag force required to fluidise the specific solid bead material is proportional to both the density and the diameter of the particle chosen.